2018
DOI: 10.1158/2326-6066.cir-17-0383
|View full text |Cite
|
Sign up to set email alerts
|

Soluble SLAMF6 Receptor Induces Strong CD8+ T-cell Effector Function and Improves Anti-Melanoma Activity In Vivo

Abstract: SLAMF6, a member of the SLAM (signaling lymphocyte activation molecules) family, is a homotypic-binding immune receptor expressed on NK, T, and B lymphocytes. Phosphorylation variance between T-cell subclones prompted us to explore its role in anti melanoma immunity. Using a 203-amino acid sequence of the human SLAMF6 (seSLAMF6) ectodomain, we found that seSLAMF6 reduced activation-induced cell death and had an antiapoptotic effect on tumor-infiltrating lymphocytes. CD8 T cells costimulated with seSLAMF6 secre… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 33 publications
0
11
0
Order By: Relevance
“…SLAMF6 has been shown to have clinical significance [3034]. In humans with X-linked lymphoproliferative (XLP) it has been demonstrated that blocking SLAMF4 and SLAMF6 via antibodies restores T cell function against B cell targets that also express SLAMF members [31].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…SLAMF6 has been shown to have clinical significance [3034]. In humans with X-linked lymphoproliferative (XLP) it has been demonstrated that blocking SLAMF4 and SLAMF6 via antibodies restores T cell function against B cell targets that also express SLAMF members [31].…”
Section: Discussionmentioning
confidence: 99%
“…In cancer, Eisenberg et al . has shown in great detail that administration of a soluble ectodomain of SLAMF6 increases the effector function CD8 + T cells against melanoma cells [34]. Furthermore, Yigit et al .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Intermediate monocytes expressed the highest levels of adenosine deaminase ( ADA ), which is reported to act as a modulator of T-cell differentiation, increasing the generation of effector, memory and regulatory T cells (133). Both ncM and intM were enriched in transcripts for SLAMF6 , reported to boost IFN-γ production and cytolytic anti-tumor activity of human CD8 T cells in vitro (134). Furthermore, expression of ALCAM , encoding a ligand for CD6 on T cells, important for stabilizing the immunological synapse between APC and T cells (135) and reported to mediate extravasation of monocytes (136), was more than 3-fold higher expressed in ncM than in cM.…”
Section: Resultsmentioning
confidence: 99%
“…Terhorst and our group have previously shown that canonical SLAMF6 serves as an inducer of T cell exhaustion and acts as an inhibitory checkpoint for T cells 13,22,23 . The results presented here with the fulllength SLAMF6 support this role.…”
Section: Trans-binding Of Full-length Slamf6 On Activatedmentioning
confidence: 94%